Si c'était à refaire Les Artistes Associés présentent une production Films 13 ; écrit, produit, et filmé par Claude Lelouch. - Lelouch, Claude, 1937-; Lai, Francis.; Gaubert, Christian.; Barouh, Pierre, 1934-; Lefrançois, Jacques.; Deneuve, Catherine, 1943-; Aimée, Anouk, 1932-; Denner, Charles.; Huster, Francis.; Briot, Jean-Jacques. (Collection Claude Lelouch., 2009)
Catherine is released from prison after serving fifteen years for murder. She had a son, Simon, while in prison. Today, she must learn how to live in freedom again, to find her place in society, and to discover this son whom she knows little about. She also becomes best friends with Sarah, who is also an ex-convict.